Effects of Proanthocyanidins on Adhesion, Growth, and Virulence of Highly Virulent Extraintestinal Pathogenic Escherichia coli Argue for Its Use to Treat Oropharyngeal Colonization and Prevent Ventilator-Associated Pneumonia. Issue 6 (June 2015) - Margetis, Dimitri; Roux, Damien; Gaudry, Stéphane; Messika, Jonathan; Bouvet, Odile; Branger, Catherine; Ponnuswamy, Padmapriya; Oufella, Hafid Ait; Dreyfuss, Didier; Denamur, Erick; Ricard, Jean-Damien
Abstract : Objective: In the context of increasing microbial resistance and limited new antimicrobials, we aimed to study the antimicrobial effects of cranberry proanthocyanidin extracts on Escherichia coli growth, adhesion to epithelial cells, and lung infection. Design: Experimental in vitro and in vivo investigation. Setting: University research laboratory. Subjects: Seventy-eight 6- to 8-week-old male Balb/C mice. Interventions: In vitro, the effect of increasing concentrations of cranberry proanthocyanidin on bacterial growth of different clinical E. coli isolates was evaluated. Ex vivo, adhesion of E. coli to fresh human buccal epithelial cells was measured in the presence or absence of cranberry proanthocyanidin using microscopy. In vivo, lung bacterial count, pulmonary immune response (neutrophil murine chemokine keratinocyte-derived cytokine measurement and polymorphonuclear recruitment in bronchoalveolar lavage fluid), and lethality were evaluated in a pneumonia mouse model with E. coli precultured with or without cranberry proanthocyanidin. E. coli isolates originated from ventilated ICU patients with respiratory tract colonization or ventilator- associated pneumonia. They differed in number of virulence genes. Measurements and Main Results: A significant inhibition of bacterial growth was observed with increasing concentration of cranberry proanthocyanidin, affecting both time to maximal growth and maximal growth rate ( p < 0.0001 for both). The minimal concentration at which this effect occurred was 250 μg/mL. Cranberry proanthocyanidin significantly reduced E. coli adhesion to fresh buccal epithelial cells by up to 80% ( p < 0.001). Bacterial counts in homogenized lungs and bronchoalveolar lavage fluid were decreased after cranberry proanthocyanidin exposition ( p < 0.05 and p < 0.01, respectively). Cranberry proanthocyanidin also decreased KC concentrations and polymorphonuclear cell recruitment in bronchoalveolar lavage fluid ( p < 0.05 for both). At identical inoculum, mortality was reduced by more than half in mice inoculated with E. coli exposed to cranberry proanthocyanidin ( p < 0.01). Conclusion: Cranberry proanthocyanidins exhibit potent effects on growth, adhesion, and virulence of oropharyngeal and lung isolates of E. coli, suggesting that cranberry proanthocyanidin could be of clinical interest to reduce oropharyngeal colonization and prevent lung infection. Abstract : Supplemental Digital Content is available in the text.